Plasmonic Particles that Hit Hypoxic Cells. (20th November 2014) - Ratto, Fulvio; Witort, Ewa; Tatini, Francesca; Centi, Sonia; Lazzeri, Lorenza; Carta, Fabrizio; Lulli, Matteo; Vullo, Daniela; Fusi, Franco; Supuran, Claudiu T.; Scozzafava, Andrea; Capaccioli, Sergio; et al.
<x xml:space="preserve">Abstract</x> The use of gold nanorods as contrast agents for the optical hyperthermia of cancer is receiving ever more attention. However, their selective delivery to tumors still remains an outstanding problem. In most cases, the identification of suitable molecular targets is complicated by the lack of qualitative differences between healthy and cancer cells. The focus of prior work has mainly been on the cancer cells per se. Instead, here, the aim is moved to secondary fingerprints that arise in response to the cancer microenvironment. One common feature of tumors is a combination of poor oxygenation and high oxygen consumption, which generates hypoxia. Hypoxic cells need to switch to an anaerobic metabolism, which is accompanied by a multitude of molecular processes, including the expression of transmembrane isoforms of carbonic anhydrases. Here, gold nanorods are conjugated with selective inhibitors of these enzymes, in order to recognize and hit hypoxic cells. The cellular uptake, cytostatic activity and capacity to impart an optical sensitization of these particles is shown to display a strong dependence on environmental oxygenation.